Beyond Oil : Kazakhstan's Path to Greater Prosperity through Diversifying, Volume 2. Main Report - World Bank (Washington, DC, 2014)
Kazakhstan aspires to become one of the world s 30 most developed economies by 2050. The focus is on laying the basis for the accelerated diversification of the economy through industrialization and infrastructure development, including enhancing human capital to drive innovation and economic efficiency. This country economic memorandum report adopts an analytical framework that looks into options that will be explored to help authorities think about diversification across three sectors: diversification of products and services; diversification of economic partners; and diversification of endowments. Five chapters structure this report, outlining the weaknesses and strengths of the Kazakh economy that will need to be addressed for increased prosperity. Chapter 1 discusses Kazakhstan s natural resources and how important it is to focus on the policies that matter for development and diversification. Chapter 2 focuses on export concentration and assesses whether resource dependence leads to macroeconomic volatility, whether Kazakhstan has been able to avoid volatility, and what macro-policy solutions are available to Kazakhstan. Chapter 3 looks at the structure of employment in the country and assesses whether Kazakh workers have the skills demanded by the market. Chapter 4 analyzes the regulatory environment and how well market institutions have developed to strengthen the quality of institutions. Chapter 5 uses the product space analysis to assess where Kazakhstan s comparative advantages are. It then discusses whether the country has faced excessive trade barriers, whether there is a role for industrial policy, and what will be done in the short term to help diversification.